Antimony production by carbothermic reduction of stibnite in the presence of lime - Padilla R.; Chambi L.C.; Ruiz M.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Experimental work on the carbothermic reduction of Sb2S3 in the presence of lime was carried out in the temperature range of 973 to 1123 K to produce antimony in an environmentally friendly manner. The results demonstrated the technical feasibility of producing antimony by this method without producing SO2 gas. Complete conversion of Sb2S3 was obtained at 1023 K in about 1000 seconds and at 1123 K in less than 250 seconds using stibnite-carbon-lime mixtures with molar ratios Sb2S3:CaO:C = 1:3:3. It was found that the reduction proceeds through the formation of an intermediate oxide SbO2, which is subsequently reduced by CO(g) to yield antimony metal and CaS. The kinetics of the Sb2S3 reduction was analyzed by using the equation ln(1-X) = -kt. The activation energy was 233 kJ mol-1 in the temperature range of 973 to 1123 K. This value would correspond to an antimony catalyzed carbon oxidation by CO2.